Research for forecasting the effect of various meteorological-dynamic conditions on the possible spreading of Cs-137 radioactive substances in case a level 7 incident occurs from Fengcheng nuclear power plant (China) - Nguyen Minh, Hai; Vu Duy , Vinh; Nguyen Trong, Ngo; Tran Quang, Thien (Vietnam Journal of Marine Science and Technology, 2023)
Because its location is quite close to the Vietnamese border, the future operation of the Fengcheng (Phong Thanh) nuclear power plant (NPP) can raise many concerns about the impact on the marine environment in case a serious incident occurs. Based on the Delft3D modeling toolkit, calculation scenarios to simulate the spreading of Cs-137 radioactive emission when a level 7 incident occurs at Phong Thanh NPP have been set up according to different dynamic/meteorological conditions presented at the time of incidents (during the northeast monsoon, transitional monsoon, or southwest monsoon) to assess/predict the possibility of radioactive emission and to spread, and their affecting the waters of Vietnam. The simulation results show that when a level 7 incident occurs from Phong Thanh NPP, the area of influence might be the entire East Sea after 3–6 months. The Gulf of Tonkin area would be contaminated with high radiation levels (300–350 Bq/m3) after about one month. The radiation would then gradually decrease to less than 150Bq/m3 after one year and below 30Bq/m3 after two years. The impacts of various dynamical and meteorological conditions on the ability to spread and disperse radioactive substances when an incident occurs are only evident in the early stages (up to 3 months after the incident). After this time, the contaminated area would cover almost the entire coastal strip of Vietnam due to a large amount of radiation, and the effects of different dynamic/meteorological conditions would be irregular.